2020
DOI: 10.1088/1757-899x/830/3/032095
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of operator reliability level using the Human Error Assessment and Reduction Technique (HEART) method

Abstract: Workers can cause harm to the company caused by human error. Human error has a close relationship with the level of reliability of a worker. One result of the low level of reliability of workers is product defects. PT. X is a company that manufactures engine and molding spare parts and dies, using automatic machinery. There are defective products on production, with an average number of defects of 1.2% per month above the disability tolerance set by the company of 0.2%. The types of defects in the product are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…di perusahaan yang memproduksi suku cadang mesin dan mesin otomatis. Kecacatan produk sekitar 1,2% disebabkan oleh human error (Rejeki et al, 2020).…”
Section: Pendahuluanunclassified
“…di perusahaan yang memproduksi suku cadang mesin dan mesin otomatis. Kecacatan produk sekitar 1,2% disebabkan oleh human error (Rejeki et al, 2020).…”
Section: Pendahuluanunclassified
“…A series of studies have been undertaken to determine the initial possibility of a failure occurring. Current research involves the study of human error in the marine industry as the cause of marine accidents [3]; maintenance operations in the marine industry [4]; calculation of human error that will cause specific grounding events [5]; the evaluation of human error in railway accidents [6,7]; human-induced actions with the potential to expose operators working in a radiation-emitting facility to radiation [8,9]; human error during the steam boiler operation [10,11]; and the human error probability in a probability security assessment of the reactor in nuclear power plants [12]. Research has Sustainability 2022, 14, 10838 2 of 16 demonstrated that the human factor is an important risk factor in an industry, regardless of production and process.…”
Section: Introductionmentioning
confidence: 99%
“…in a company that manufactures auto parts and machinery. Product defects about 1.2% are caused by human error (Rejeki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%